Event Logistics in Sustainability of Football Matches - Emy Ezura A Jalil; Liau Shiau Hui; Ku Eet Ning; Lee Khoon Fai (International Journal of Supply Chain Management, 2019)
The sports event is the most popular and well-known event by the people since the past few decades. The most significant sports events will draw billion of the spectators to attend it. However, it is difficult to maintain the sustainability of the events without proper event management which may bring consequences to the economics, society and the environments. The sustainable of events are closely related to the event logistics. The purpose of this study is to explore the relationship between the sustainability of sports matches and event logistics in term of accessibility, information and communication technology (ICT) and waste management. The results obtained from the respondents of the population sample of the football audience by using a quantitative approach through online survey design. The result supported the awareness level of event organisers implicate the sustainability of an event and provide evidence that encapsulated event management and event logistics importance to the public.